2012
DOI: 10.2139/ssrn.2158300
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment and Vocational Training

Abstract: Youth Unemployment and Vocational Training 1This paper focuses on the determinants of the labor market situation of young people in developed countries and the developing world, with a special emphasis on the role of vocational training and education policies. We highlight the role of demographic factors, economic growth and labor market institutions in explaining young people's transition into work. We then assess differences in the setup and functioning of the vocational education and training policies in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 61 publications
0
23
0
2
Order By: Relevance
“…Studies manifest that vocational training promotes the employability of youth in various countries. For instance, Biavaschi et al (2012) confirmed the contribution of vocational training on youth employment in South and Sub-Saharan Africa, Hirshleifer et al (2014) in Turkey, Batchuluun, et al(2017) in Mongolia and Barrera-Osorio, et al (2020) in Colombia.…”
Section: The Concept Of Vocational Education Trainingmentioning
confidence: 68%
See 1 more Smart Citation
“…Studies manifest that vocational training promotes the employability of youth in various countries. For instance, Biavaschi et al (2012) confirmed the contribution of vocational training on youth employment in South and Sub-Saharan Africa, Hirshleifer et al (2014) in Turkey, Batchuluun, et al(2017) in Mongolia and Barrera-Osorio, et al (2020) in Colombia.…”
Section: The Concept Of Vocational Education Trainingmentioning
confidence: 68%
“…Biavaschi et al (2012) asserted that in South and Sub-Saharan Africa, as a strategy to curb youth unemployment challenges, local networks and NGOs conduct informal apprentice training to familiarize the trainee with new technologies which facilitates easier access of credit and acquizition of modern working equipment.Joseph Magali, PhD & Christopher Mbagwa (2021), Paper Title: The Influence of Youth Economic Empowerment Project on Employability of Youth in Tanzania: A Case of Ilala Municipality. Business Education Journal (BEJ), Volume 10, Issue III, 11 Pages.…”
mentioning
confidence: 99%
“…Different stakeholders argued that the reason for these numbers was an absence of work ethic and general lack of motivation among young people in Georgia (S4, S7). They implied that individuals just need to work harder and become more resilient for the economy to grow more sustainably, ignoring cultural factors as well as historic and institutional specificities that are often engrained in the social structure through unwritten norms and behaviors (Acemoglu, et al, 2005;Acemoglu & Robinson, 2012;Biavaschi, et al, 2012;Greif, 2006;North, 1990). This distinction between an individual choice taking place in a decision-making vacuum unimpeded by outside factors, or it taking place under consideration of the mores and cultural factors of the country is an important one, because the former view is a reflection of a deeply entrenched absorption of a neoliberal view of individualism in society.…”
Section: Easing Unemploymentmentioning
confidence: 99%
“…Second, the strong and positive effect of collective training systems on spending on active labour market policies is remarkable. Countries with collective training systems usually have the lowest youth unemployment numbers anywhere in the world (Biavaschi et al 2012;G. Martin 2009), and the systems have been praised for offering young people without tertiary education a pathway into stable and well-paid employment (Busemeyer 2015;Iversen 2005;Soskice 1994).…”
Section: Contributions and Relevancementioning
confidence: 99%
“…This is not a new conclusion. Conventional wisdom holds that countries with collective training systems have lower rates of youth unemployment because the employer-organised training reduces skill mismatches and thereby smooths the transition from school to work (Biavaschi et al 2012;Breen 2005;Gangl 2003;G. Martin 2009).…”
Section: For Young Peoplementioning
confidence: 99%